Privacy of European citizens in the face of the development of new data-driven business models - Radosław Wisniewski; Inga Oleksiuk; Bożena Iwanowska (Contemporary Economics, 2021)
The main objective of the paper is to identify the imbalance between the right to privacy and the business objectives of entities creating new Data-Driven Business Models (DDBMs) of consumers (EU citizens). Information about the consumer and their characteristics has nowadays become a service or market commodity thanks to which new economic processes, based on the use of advanced data processing technologies, are created. In digital space, new types of DDBM are established, which provide entrepreneurs with added value, based on the mass use of the consumer's data collected often without their knowledge, on the margins of legality. This paper analyzes the impact of the development of DDBMs on selected privacy areas: personal data, the right to be forgotten, confidentiality of communications, one's image and identity. In each of these areas, situations are identified that indicate a progressive re-evaluation of citizens' privacy rights. The authors suggest that disruption of the balance between the right to privacy and business objectives may lead to unambiguous consequences, not only for the consumer (EU citizen), but also for the business entities.
Keywords: D18; M2; M13; 330; Data-Driven Business Models; right to privacy; personal information; right to be forgotten; confidentiality of communications; image; identity